Modern electrochemistry: interdisciplinary research at the forefront of science. - Kolb, D; Amatore, C; Compton, R (2010)
Over the last 50 years, electrochemistry has undergone remarkable changes: From thermodynamics to structure studies with atomic resolution, from Gouy–Chapman models to ab initio density functional theory. Its previous boundaries, which defined electrochemistry as one of the four pillars of physical chemistry, became increasingly transparent and nowadays modern electrochemistry is highly interdisciplinary, interacting with neighboring sciences such as nanoscience, materials science, life and environmental science—and not the least with energy science, where electrochemistry currently receives an unusually high attention from all levels/sides of our society. [to continue reading visit http://onlinelibrary.wiley.com/doi/10.1002/cphc.201000616/epdf]